The role of bioindicators and the modern instrumental methodology of 1H NMR applied in ecological forensic expertise - Viorica Trifăuțan; Elena Gorincioi; Boris Nedbaliuc (Acta et Commentationes Exact and Natural Sciences, 2023)
Bioindicators and NMR performance offer new possibilities for forensic examination, directly in nature, at the site of the incident/ecological impact aimed at quickly finding out the truth about the crime and the criminal. The advantage of using biotic parameters (bioindication) lies in their greater objectivity and validity. The state of the boita is determined by the general state of the environment and promptly reacts to negative actions from various sources.